2008
DOI: 10.1007/s10661-008-0269-7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pH and temperature on the aqueous geochemistry of neodymium in near surface conditions

Abstract: Geochemical calculations were employed for the solubility and speciation of neodymium in a model soil solution as a function of pH. The calculations were based on the recently determined stability constants for Nd and solubility product for the Nd end-member of mineral monazite (NdPO(4)). Simulations were carried out at near neutral pH (pH 6.0 to pH 7.5) and 25 degrees C at the atmospheric CO(2) partial pressure. Additional calculations were also performed to assess Nd mobility at the extreme temperature condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
(20 reference statements)
1
6
0
Order By: Relevance
“…However, both the adsorption of Nd complexes trench minerals and precipitation of secondary Nd-containing solids were likely to be important contributors. The rapid removal immediately after injection aligns with research, which has shown that Nd (and contaminant counterparts Pu and Am) strongly sorb to a variety of mineral phases including phosphates and carbonates 28,81 as well as iron and manganese oxides. 82,83 Although the system is unlikely to be at thermodynamic equilibrium, such calculations may provide insight into the processes responsible for the Nd concentrations within the trench.…”
Section: ■ Results and Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…However, both the adsorption of Nd complexes trench minerals and precipitation of secondary Nd-containing solids were likely to be important contributors. The rapid removal immediately after injection aligns with research, which has shown that Nd (and contaminant counterparts Pu and Am) strongly sorb to a variety of mineral phases including phosphates and carbonates 28,81 as well as iron and manganese oxides. 82,83 Although the system is unlikely to be at thermodynamic equilibrium, such calculations may provide insight into the processes responsible for the Nd concentrations within the trench.…”
Section: ■ Results and Discussionsupporting
confidence: 79%
“…In addition to sorptive processes, precipitation of secondary Nd phases, particularly Nd phosphate and to a lesser extent Nd carbonate, could also account for the lower concentrations of dissolved Nd measured in the trench (relative to Sr and Cs). Thermodynamic calculations predicted that even in the presence of only minor phosphate concentrations (Table S3.1), Nd almost entirely partitioned as the oversaturated solid-phase NdPO 4 (Figure S3.6), a mineral known to readily precipitate in near-surface environments …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cteiner [42] , oxalate, and acetate on monazite solubility. At pH levels ranging from 6.0 to 6.5, Nd (oxalate) was the dominant species, followed by Nd 3+ and NdSO 4 + .…”
Section: Rare Earth Element Abundances In Natural Waters: Groundwatermentioning
confidence: 98%
“…Cteiner [27] , oxalate and acetate on solubility. At pH levels ranging from 6.0 to 6.5 Nd(oxalate) was the dominant species, followed by Nd 3+ and NdSO 4 + .…”
Section: Reactions Involving Organic Complexationmentioning
confidence: 98%